Answer:
Option C. f¯¹(x) = (5x + 3)/2
Step-by-step explanation:
f(x) = (2x – 3)/5
We can obtain the inverse of the above equation as follow:
Let f(x) be y.
Therefore,
F(x) = (2x – 3)/5
y = (2x – 3)/5
Next, we shall interchange the position of 'y' and 'x'. This is illustrated below:
y = (2x – 3)/5
x = (2y – 3)/5
Next, we shall make y the subject of the expression. This is illustrated below below:
x = (2y – 3)/5
Cross multiply
2y – 3 = 5x
Rearrange
2y = 5x + 3
Divide both side by 2
y = (5x + 3)/2
Therefore, the inverse of
f(x) = (2x – 3)/5 is f¯¹(x) = (5x + 3)/2